Innovation as a Mediation to Improve Business Performance with The Antecedents of Technological Ability and Absorptive Capacity - Fairuska Alifa Aurel; Aji Alfyan Bayu; Azka Muhammad Gilang Maulana (SHS Web of Conferences, 2025)
Innovation plays an important role in improving business performance, especially for SMEs facing fierce competition and rapid market changes. Technological capability and absorptive capacity are the main factors that influence how SMEs can innovate and adapt to technological developments and new information. The purpose of this paper is to explore the role of innovation as a mediator in improving SME business performance through the influence of technological capability and absorptive capacity. This study focuses on SMEs in certain regions, with samples taken using the Hair et al., (2018) method and involving a minimum of 100 respondents. The data analysis technique was carried out using SEM-PLS 4.0. The implications of this study indicate that SMEs that are able to develop technological capabilities and strengthen their absorptive capacity will be better able to innovate, which in turn will improve their business performance. This study offers new insights into how innovation can be maximized through optimizing the company’s internal capabilities, especially among SMEs, which are rarely discussed in previous studies.